Pengaruh Pendidikan Kesehatan terhadap Pengetahuan Ibu tentang Pemberian Vitamin A pada Balita Usia 12-59 Bulan di Wilayah Kerja Puskesmas Sengeti Desa Pematang Pulai - Marta Suri; Vevi Suryenti Putri; Della Anggita (Prosiding Seminar Kesehatan Nasional, 2022)
Vitamin A is one of the nutrients from the vitamin group that is needed by the body which is useful for eye health and for body health (increases the body's resistance to fight diseases such as measles, diarrhea and other infectious diseases). to prevent vitamin A deficiency in infants. Based on data obtained from the Sengeti Health Center in February 2021, the number of toddlers who received vitamin A in Pematang Pulai Village was only 63 out of a total of 92 toddlers with a percentage of 68.48%, the achievement of vitamin A administration in Pematang Pulai Village was still below the national achievement target i.e. 87%. The purpose of this study was to determine the effect of health education on mothers' knowledge about giving vitamin A to toddlers aged 12-59 months in the Working Area of the Sengeti Health Center, Pematang Pulai Village. Quantitative with a one group pre-test post-test pre-experimental research design. The population of this study were all mothers with toddlers aged 12-59 months in Pematang Pulai Village with a sample of 18 people using a purposive sampling technique. Data collection was done by filling out a questionnaire and analyzed Pre and Post by using a paired sample t-test. Shows that the average knowledge of mothers before attending health education was 12.83 and after attending health education the average knowledge of mothers increased to 15.33. The results of the t-test statistical test obtained p-value = 0.000 <0.05. There is an effect of health education on mother's knowledge about giving vitamin A to toddlers aged 12-59 months in Pematang Pulai Village